Public Sentiment Analysis of the Rupiah Redenomination Policy Discourse Using IndoBERT on Social Media Data - Azkar Rindra Maulana; Aliffian Alfarish; Gibran Abdillah (Journal Collabits, 2026)
The discourse on rupiah redenomination has regained momentum in the 2025–2027 policy agenda, with the discussion of the draft regulation on “Rupiah Price Changes.” In legislative studies, redenomination is positioned as a measure to simplify nominal values in order to improve the efficiency of transactions, accounting, and financial system operations, one of which is through the removal of three zeros from the rupiah [1]. On the other hand, Bank Indonesia emphasizes that redenomination is different from sanering because it does not aim to reduce people's purchasing power, but rather to simplify nominal values in stable economic conditions [2]. It is important to emphasize this difference in concept because the public often equates the “removal of zeros” with a reduction in value, giving rise to concerns that are not always in line with the definition of the policy.